You Should Be At Home Instead!: : A Comparative Analysis of Varda’s The Vagabond (1985) and Zhao’s Nomadland (2020) - Dymussaga Miraviori, Areispine (IMAJI, 2022)
In 1985, Agnes Varda released The Vagabond, a film about a young woman who chooses to wander the country alone and is found dead in the winter. Thirty five years later, Chloe Zhao released Nomadland (2020), a film about a middle aged woman who had to live in an RV because her husband died and the company shut down and discontinued the workers’ residence where she lived. These two films have similarity: a woman lives alone on the street without a house. This paper wants to examine how women without a house are perceived and have more chance and risk to be failed by the patriarchal society.